2015
DOI: 10.3390/s150614526
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Voltammetric/Amperometric Determination of Sulfide and Nitrite in Water at BDD Electrode

Abstract: This work reported new voltammetric/amperometric-based protocols using a commercial boron-doped diamond (BDD) electrode for simple and fast simultaneous detection of sulfide and nitrite from water. Square-wave voltammetry operated under the optimized working conditions of 0.01 V step potential, 0.5 V modulation amplitude and 10 Hz frequency allowed achieving the best electroanalytical parameters for the simultaneous detection of nitrite and sulfide. For practical in-field detection applications, the multiple-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…22 The working potential was determined by scanning potential in the range from 0.5 V to 1.0 V with a step of 50 mV in 0.1 mol×L -1 PBS in the presence of 10 -4 mol×L -1 melatonin ( Figure 7). The dependence from the data obtained, current vs potential, revealed that the optimal working potential for oxidation of melatonin is 0.8 V.…”
mentioning
confidence: 99%
“…22 The working potential was determined by scanning potential in the range from 0.5 V to 1.0 V with a step of 50 mV in 0.1 mol×L -1 PBS in the presence of 10 -4 mol×L -1 melatonin ( Figure 7). The dependence from the data obtained, current vs potential, revealed that the optimal working potential for oxidation of melatonin is 0.8 V.…”
mentioning
confidence: 99%
“…Anamaria et al. reported voltammetric‐ and amperometric‐based sensors using a commercial BDDE for simultaneous detection of nitrite and sulfide in water [49] . The determination and direct electro‐oxidation of nitrite and sulfide were probed by CV and square‐wave‐ and differential‐pulsed voltammetry techniques.…”
Section: Sulfide Sensing Strategies In Controlled Potential Techniquesmentioning
confidence: 99%
“…The key to successful application of electrochemical methods in pesticides detection is adequate electrode material. The boron-doped diamond electrode (BDD) is recognized as one of the most versatile electrode materials used in electroanalysis, due to its wide potential window in aqueous solution, low background currents, and long-term stability [ 13 , 14 , 15 ]. Very promising results have been found for BDD application in the electrochemical detection of pesticides [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%